The interdependence of politics and administration - Riggs, Fred W. (1987)
The politics/administration dichotomy persists because it is maintained by the confusion in the distinction between politics and administration and doctrine of "separation of powers" which was designed to safeguard human rights and civil liberties against the power of despotic rulers and despotic "majorities." It is even strengthened by the American career bureaucrats who protect the status they had achieved through the merit system and the academic addiction to the dichotomy myth. A theory of interdependence is necessary and can be achieved by focussing on the bureaucracy and emphasizing the "unity rule,". Officials who administer best are politically competent also.
Keywords: Politics and administrative dichotomy; Bureaucracy